Culturally-Inspired Low-Cost Housing Solutions: An Afrocentric Approach for Kano, Nigeria - Abdulkarim Aliyu, Aisha; Salma Zubair, Mahmud (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
ABSTRACT Significant cities in developing countries are undergoing an enormous migration of people from countryside regions. This migration from the countryside was mainly to develop careers and expect a higher salary for survival. This is vital in the Kano region, Africa, which annually indicates a large influx of low-income immigrants to urban cities, resulting in a lack of affordable housing to accommodate these immigrants' needs. Qualitatively the low-cost housing in Kano Nigeria, and many countries in Africa, has not been satisfactory to the family housing needs like comfort, social, cultural, and religious demand. The focus of the paper is to identify the importance of the Afrocentric cultural approach to spatial development in low-cost housing schemes where two existing case studies are carried out within the Kano metropolitan using a mixed methodology approach (document analysis and direct–observation) through the hermeneutic research paradigm. Findings relating to better space-making for low-income housing design projects transitioning to an Afrocentric cultural lifestyle was highlighted. This study may help in constructing a new development scheme towards the approach of consciously designed low-cost housing with a sense of Afrocentric culture according to the needs of the African people. By having a deeper understanding of the African people's needs, the outcome of the future built environment can provide more than just the minimum requirement for low-cost housing but instead focuses on the sense of community role for its design emphasis. The government and relevant authorities should work with low-cost housing providers, developers, and designers to provide better living places to elevate the quality of life for African society towards positive living and improve their health development.